β-Asarone Ameliorates β-Amyloid-Induced Neurotoxicity in PC12 Cells by Activating P13K/Akt/Nrf2 Signaling Pathway - Miaomiao Meng; Lijuan Zhang; Di AI; Hongyun Wu; Wei Peng (Frontiers Media S.A., 2021)
Accumulation of β-amyloid (Aβ) causes oxidative stress, which is the major pathological mechanism in Alzheimer's disease (AD). β-asarone could reduce Aβ-induced oxidative stress and neuronal damage, but the molecular mechanism remains elusive. In this study, we used an Aβ-stimulated PC12 cell model to explore the neuroprotective effects and potential mechanisms of β-asarone. The results showed that β-asarone could improve cell viability and weaken cell damage and apoptosis. β-asarone could also decrease the level of ROS and MDA; increase the level of SOD, CAT, and GSH-PX; and ameliorate the mitochondrial membrane potential. Furthermore, β-asarone could promote the expression of Nrf2 and HO-1 by upregulating the level of PI3K/Akt phosphorylation. In conclusion, β-asarone could exert neuroprotective effects by modulating the P13K/Akt/Nrf2 signaling pathway. β-asarone might be a promising therapy for AD.